Inhibition of Listeria monocytogenes by Phage Lytic Enzymes Displayed on Tailored Bionanoparticles - Stone E; Pennone V; Reilly K; Grant IR; Campbell K; Altermann E; McAuliffe O (MDPI (Basel, Switzerland), 2022)
The high mortality rate associated with Listeria monocytogenes and its ability to adapt to the harsh conditions employed in food processing has ensured that this pathogen remains a serious problem in the ready-to-eat food sector. Bacteriophage-derived enzymes can be applied as biocontrol agents to target specific foodborne pathogens. We investigated the ability of a listeriophage endolysin and derivatives thereof, fused to polyhydroxyalkanoate bionanoparticles (PHA_BNPs), to lyse and inhibit the growth of L. monocytogenes. Turbidity reduction assays confirmed the lysis of L. monocytogenes cells at 37 °C upon addition of the tailored BNPs. The application of BNPs also resulted in the growth inhibition of L. monocytogenes. BNPs displaying only the amidase domain of the phage endolysin were more effective at inhibiting growth under laboratory conditions (37 °C, 3 × 107 CFU/mL) than BNPs displaying the full-length endolysin (89% vs. 83% inhibition). Under conditions that better represent those found in food processing environments (22 °C, 1 × 103 CFU/mL), BNPs displaying the full-length endolysin demonstrated a greater inhibitory effect compared to BNPs displaying only the amidase domain (61% vs. 54% inhibition). Our results demonstrate proof-of-concept that tailored BNPs displaying recombinant listeriophage enzymes are active inhibitors of L. monocytogenes.
Keywords: BNPs; Listeria monocytogenes; amidase; bacteriophage; bionanoparticles; endolysin